A Metaheuristic Optimization Using Explosion Method On A Hybrid Pd2-Lqr Quadcopter Controller - Raihan, Mohamad Norherman Shauqie Mohamed (2021)
The popularity of the rotorcraft type UAV, the quadrotor, has grown rapidly in recent years due to its advantages and capability to perform various applications such as environment monitoring, surveillance, and inspection. However, the quadrotor’s dynamics are highly nonlinear and underactuated since it has 6 DOF that need to be controlled by only 4 actuators. Besides, it is also crucial that the controller’s gains are tuned appropriately since it can affect the quadrotor’s performance. This study aims to develop an effective optimal control technique to control and stabilize the quadrotor's altitude and attitude motion. A simulation-based experiment in MATLAB/Simulink environment was conducted to test and verify the proposed algorithm and controller performance. The mathematical model of the quadrotor was derived based on the Newton-Euler approach and linearized using a small angle approximation. In this study, a Hybrid PD2-LQR controller was proposed for quadrotor control and stabilization. Conventionally, the controller’s gains were tuned using the trial-anderror method. The problem with this method was that it very time-consuming, and the control designer could never tell which gains are the optimal solution for the controller. Therefore, an optimization algorithm based on the explosion method called REA was proposed and implemented on the proposed Hybrid PD2-LQR control structure. A comparative study with 8 well-known algorithms, PSO, ABC, GA, DE, MVO, MFO, FA, and STOA, was performed to evaluate the performance of the proposed algorithm. Similarly, the proposed controller was evaluated by a comparative study with 6 conventional controllers, PD, PID, LQR, Hybrid P-LQR, Hybrid PD-LQR, and Hybrid PD2-LQR. The findings show that the REA could perform well in exploiting the global optimum and exploring the search space. The convergence speed of the REA was also faster than other algorithms. Similarly, for the controller, the findings show that the REA-based Hybrid PD2-LQR controller has a faster rise time with a shorter settling time than the conventional controllers, while there was no overshoot and steady-state error produced. On average, the rise time, settling time, overshoot, steady-state error and RMSE was improved by 95%, 95.3%, 100%, 100%, and 43.5% respectively for roll and pitch motion, while 96.5%, 96.5%, 100%, 97.2%, and 47.3% respectively for yaw motion. For altitude motion, the rise time, settling time, overshoot, and steadystate error were improved by 84.5%, 85.5%, 100%, and 100%, respectively. The RMSE for altitude motion was not improved but still could be accepted since the difference with the conventional controllers was not too much. Therefore, based on these findings, it could be concluded that the proposed REA-based Hybrid PD2-LQR controller was the best among the tested controller and suited for controlling and stabilizing the quadrotor’s altitude and attitude motion since it could significantly improve the performance of the quadrotor’s response.